1980
DOI: 10.1128/iai.27.3.988-994.1980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Hit from the Alpha Hemolysin Produced by Escherichia coli on the Morphology of Sheep Erythrocytes

Abstract: Scanning electron micrographs of sheep erythrocytes showed that attachment of the alpha hemolysin produced by Escherichia coli resulted in the formation of spherocytes, with 10 to 20 small projections spaced relatively evenly over the surface of the erythrocyte membrane. This shape change was induced within 5 min after treatment. If the hemolysin concentration was reduced to a level which would lyse only a fraction of the total erythrocytes, the affected cells were easily identified aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In contrast to the large amount of molecular genetical data available on ECH, information on the mechanism of its cytolytic action and on its biological effects in a physiological environment has been scarce . Following earlier reports that together had suggested a membrane-perturbating effect ofECH on erythrocytes (21)(22)(23)(24), we recently showed that ECH forms discrete hydrophilic transmembrane pores of ti2 nm effective diameter both in erythrocyte membranes (25) and in planar lipid bilayers (26). These pores are probably generated by the insertion oftoxin monomers into the bilayer; in this respect, they differ from oligomerizing pore-formers including C5b-9 complement complexes (27), lymphocytolysins (28), and cytolysins of Grampositive organisms (29)(30)(31)(32)(33).…”
mentioning
confidence: 64%
“…In contrast to the large amount of molecular genetical data available on ECH, information on the mechanism of its cytolytic action and on its biological effects in a physiological environment has been scarce . Following earlier reports that together had suggested a membrane-perturbating effect ofECH on erythrocytes (21)(22)(23)(24), we recently showed that ECH forms discrete hydrophilic transmembrane pores of ti2 nm effective diameter both in erythrocyte membranes (25) and in planar lipid bilayers (26). These pores are probably generated by the insertion oftoxin monomers into the bilayer; in this respect, they differ from oligomerizing pore-formers including C5b-9 complement complexes (27), lymphocytolysins (28), and cytolysins of Grampositive organisms (29)(30)(31)(32)(33).…”
mentioning
confidence: 64%
“…Considering what is known about the lytic activity and kinetics of the E. coli hly, this appears to be a logical finding. Several groups have provided evidence that the E. coli hly exhibits a one-hit phenomenon that is easily saturable (5,11). This suggests a nonenzymatic, membrane insertional-type event similar to complement-mediated lysis.…”
Section: Resultsmentioning
confidence: 99%
“…We extended these studies by presenting evi-dence that the toxin forms fairly large, hydrophilic pores approximately 2 nm in diameter in both biological membranes (2) and protein-free, artificial lipid bilayers (27). In contrast to the oligomeric, structured pores formed by many cytolysins from gram-positive organisms (1, 3-5, 13) as well as by complement (3) and lymphocytolysins (16), the pores formed by E. coli hemolysin appeared to be generated by toxin monomers (2,19,26,27). The pores exhibited a marked selectivity for cations over anions, and pore opening was voltage dependent (27).…”
mentioning
confidence: 89%